In Silico Design of New Monoglyceride Vanillate as Anti-Methicillin Resistant Staphylococcus aureus with Molecular Docking and Molecular Dynamic Approach: In Silico Design of New Monoglyceride Vanillate - Nitbani, Febri Odel; Tjitda, Putra Jiwamurwa Pama; Ola, Pius Dore; Hahuly, Mayavira Veronica (Iranian Journal of Pharmaceutical Sciences, 2024)
New medicines for Staphylococcus aureus strain resistance are being developed using an in silico approach, modifying monoglyceride with vanillic acid to balance hydrophilic and hydrophobic properties. Furthermore, the structure of the design compounds (M1-M9) was optimized using the AM1 method and docked to Staphylococcus aureus penicillin-binding protein 2a (SauPBP2a) (PDB ID: 1mwt) as a receptor. The binding energy and molecular interaction were evaluated and compared to Penicillin G as a standard. The best dock score of a designed compound is used to evaluate its complex stability using molecular dynamics simulation. The docking results revealed that the monoglyceride containing vanillic acid improved the interaction with the receptor. Increasing the number of methylene chains (-CH2-) in the acyl group on the saturated product reduced binding energy. The outcomes also demonstrated that monorisinoleylvanillate (Compound M9), an unsaturated monoglycerylvanillate, exhibited the best binding energy of -7.1 kcal/mol. Ser462 and Asn464 are two important amino acids for catalytic domains that interact well with the product, having binding distances of 2.64 and 2.01, respectively. The M9 compound was the most stable SauPBP2a complex among design compounds, as confirmed by molecular dynamics simulation using CABS-Flex and the iMODS server. This compound will be synthesized using vanillic acid and methyl ricinoleate, and its activity against MRSA will be validated through in vitro assays in subsequent research.